resenha do livro: A Daughter of Han: The Autobiography of a Chinese Working Woman (From the Story Told Her by Ning Lao T’ai-t’ai) - Zaratin, Terezinha Naked (Revista de História, 1976)
resenha do livro PRUITT, Ida. A Daughter of Han — The Autobiography of a Chinese Working Woman. (From the Story Told Her by Ning Lao T'ai-t'ai). Stanford, Stanford University Press, 1967, 254 págs.